2010
DOI: 10.1002/jnr.22326
|View full text |Cite
|
Sign up to set email alerts
|

Role of MEK‐ERK pathway in morphine‐induced conditioned place preference in ventral tegmental area of rats

Abstract: A major goal of research on drug addiction is to develop the effective treatments to deal with the long-term behavioral disorders especially reinstatement induced by the addictive drugs such as opiates, cocaine, and cannabinoid. The molecular mechanisms underlying these substance-related disorders remain unclear so far. Here we used the model of morphine-induced conditioned place preference (CPP) in rats to mimic the progress of drug-taking, withdrawal and relapse in human. The tissue of ventral tegmental area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 67 publications
4
20
0
Order By: Relevance
“…2) showed that morphine-treated rats had a significant preference to the morphine-paired compartment (t (6) = 6.882, p b 0.01) whereas rats in the saline group had no such preference (t (6) = 1.982, p N 0.05). These results showed that morphine CPP can be successfully established using our CPP protocol, as shown in previous studies (Lin et al, 2011;Lin et al, 2010).…”
Section: The Establishment Of Morphine-induced Cppsupporting
confidence: 79%
See 1 more Smart Citation
“…2) showed that morphine-treated rats had a significant preference to the morphine-paired compartment (t (6) = 6.882, p b 0.01) whereas rats in the saline group had no such preference (t (6) = 1.982, p N 0.05). These results showed that morphine CPP can be successfully established using our CPP protocol, as shown in previous studies (Lin et al, 2011;Lin et al, 2010).…”
Section: The Establishment Of Morphine-induced Cppsupporting
confidence: 79%
“…1. In experiment 1, sixteen rats (initially 8 in each group) were first used to establish morphine-induced CPP based on the modified protocol described in previous studies (Lin et al, 2011;Lin et al, 2010). In experiment 2, to test the effect of chloral hydrate on CPP, another 23 rats were randomly assigned to three groups.…”
Section: Experimental Designmentioning
confidence: 99%
“…The blockade of NMDA receptor with MK801 or the suppression of ERK pathway with U0126 not only inhibits ERK activation but also blocks morphine-induced CPP behavior in the short (1 day) and long (7 days) post-training time, further supporting the notion that the NMDA receptor-ERK signal pathway is essential for the expression of morphine-induced CPP. It is well known that the activated MEK-ERK pathway in the different brain regions is involved in the drug addiction behaviors, in the morphine-induced reinstatement (Lin et al 2010), the reconsolidation of a cocaine-CPP task alone (Miller and Marshall 2005), the reconsolidation of a cocaine-CPP task activated by both the drug and the CPP context (Valjent et al 2006) and neuronal morphological changes after repeated exposure to cocaine (Ren et al 2010). NMDA glutamate receptors are necessary for the induction of ERK activation during cocaine-induced pronounced context-dependent of locomotor sensitization (Valjent et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Following chronic morphine expose, p -ERK1 and p -ERK2 protein levels, but not total ERK1 and total ERK2 levels, were decreased in the NAc, and the protein expression levels of total or phosphorylated ERK1 and ERK2 in the CPu were not altered (Muller and Unterwald, 2004). In the VTA, no change of total ERK1 and ERK2 protein expression levels was observed in the progress of morphine-induced CPP (Lin et al, 2010). Although total ERK1 and total ERK2 protein levels do no significantly change during addiction, it is not clear whether the transcript levels of these proteins are altered under the same conditions.…”
Section: Introductionmentioning
confidence: 99%